Economic Value Added (EVA) dan Market Value Added (MVA) pada Perusahaan Telekomunikasi yang Listing di Bursa Efek Indonesia - Fadilah, Kuni; ati, Sumi (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research is puspose to understand about finance performance of telecomunication company whom listed in BEI (Bursa Efek Indonesia). To survey that finance performance we used EVA (economic value added) and MVA (market value added).  EVA is the meansures of economic value added which made by corporate as impact of the firm activity and strategy, MVA meansures how much market value added  from companies that can be given for investor.  EVA is calculated from the result of reduction between Net Operating Profit After Tax (NOPAT) and Cost of Capital.  This research  used a descriptive  kuantitative method. The period of study are 2009-2011 year. The result of this  research show that  three from five companies  of telecomunication  corporate  is  whom  listed in BEI 2009-2011  had positive EVA. And all  of  them  had positive MVA. This was showed  that all telecomunication companies able to create resource value added for the investor. EVA >  0 is indicate that the companie has good perfomance finance and afford to create economic value added for investor.  MVA  > 0 is indicate that corporate able to create market value added for the investor. Keywords  : Economic Value Added  (EVA), Market Value  Added (MVA), Net Operating Profit After Tax(NOPAT)